Comparison between high-performance liquid chromatography and chemiluminescent immunoassay platforms in determining vitamin D levels in healthy population - Mahmud, Arif; Md Mohosin Ul Haque, Wasim; Faruque Pathan, Md (BIRDEM Medical Journal, 2024)
Background: Accurate measurement of serum vitamin D level is crucial for diagnosis and managing vitamin D deficiency, as associated with various health problems. High-performance liquid chromatography (HPLC) is commonly used methods for measuring serum vitamin D levels, but limited research has compared their performance with other available and reasonably less expansive method of testing Vitamin D levels like, Chemiluminescent immunoassay (CLIA). This study is intended to see the reliability of CLIA method compared with HPLC in measuring serum 25-hydroxyvitamin D [25(OH)D] levels in apparently healthy individuals. Methods: In this analytical cross-sectional study, we evaluated the reliability of CLIA method and compared to HPLC as standard, in measuring serum 25-hydroxyvitamin D [25(OH)D] levels among apparently healthy individuals. Serum samples from 76 participants were analyzed using both HPLC and CLIA. Results: In the HPLC method, the mean ± SD and median of 25(OH)D levels were 24.73 ± 17.80 ng/ml and 19.67 ng/ml, respectively. In the CLIA method, the mean ± SD and median of 25(OH)D levels were 29.96 ± 21.59 ng/ml and 22.59 ng/ml, respectively. Our results showed differences in mean and median values of 25(OH) D levels between the two methods, with higher values obtained from CLIA. However, there was a significant correlation between results obtained from both methods, indicating reasonable diagnostic accuracy. The coefficient of variation was higher in CLIA, suggesting higher variability in measurements. The Intraclass Correlation Coefficient for consistency was high in both methods, indicating good agreement between repeated measures. The Area Under the Curve for differentiating normal or low 25(OH) D levels and determining deficiency or not was high for both methods, indicating good diagnostic performance. Conclusion: Our study suggests that while there are differences in results between CLIA and HPLC methods for measuring serum vitamin D levels, both methods show reasonable diagnostic accuracy in a real-world clinical setting. Factors such as laboratory setup, resource availability, and population characteristics should be considered when choosing a method for measuring serum vitamin D levels. BIRDEM Med J 2024; 14(1): 38-42